Comparison of telomere length and telomerase activation between breast fibroadenoma and infiltrating ductal carcinoma in Malaysian women - Looi, L.; Cheah, P.; Ng, M.; Yip, C.H.; Mun, K.; Rahman, N.A. (West Asia Organization for Cancer Prevention, 2010)
A study was initiated to explore possible differences in handling telomere attrition in the most common lignant and benign tumours of the breast in Malaysian women. Infiltrating ductal carcinoma (IDC) and fibroadenoma (FA) represented the malignant and benign prototypes respectively. 29 IDC, 28 FA and 22 benign non-lesional control (BNL) breast tissue samples were analysed for telomerase activation using a Telomerase PCR ELISA kit (Boehringer Mannheim). In addition, 23 IDC, 12 FA and 14 BNL were subjected to telomere length determination with a TeloTAGGG Telomere Length Assay Kit (Roche Diagnostic GmbH, Germany), following digestion of genomic DNA by frequently cutting restriction enzymes RsaI and HinfI. Mean telomerase activity in IDC (A450nm=0.3338), but not FA (A450nm=0.0003) was significantly raised (p<0.05) compared with BNL (A450nm=0.0031). Similarly IDC (1.2 kb), but not FA (2.2 kb), showed significant telomere shortening (p<0.05) relative to BNL (2.9 kb). The findings imply that telomere attrition and telomerase activation differ between malignant and benign tumours of the breast and may be important for targeted therapy.